The Overview of Final Student Self-Efficacy towards Lectures - Indah Rahmi Inayati (Universitas Ahmad Dahlan, 2022)
This article aims, first to describe the self-efficacy of final-semester students in lectures based on Albert Bandura's personality theory, second describe the factors that influence the self-efficacy of final students toward lectures based on Albert Bandura's personality theory. This study was qualitative and descriptive. The primary data sources in this study were students’ perceptions of their efficacy. Data collection was conducted through interviews with the final students as research subjects. Validation technique using triangulation. The results of the study, first final semester students have low self-efficacy and high self-confidence, second factors that influence student self-efficacy are lack of experience in mastering something, and social model modeling social persuasion.